Aerosolized Bovine Lactoferrin Counteracts Infection, Inflammation and Iron Dysbalance in A Cystic Fibrosis Mouse Model of Pseudomonas aeruginosa Chronic Lung Infection - Cutone, Antimo (Int J Mol Sci, 2019)
Cystic fibrosis (CF) is a genetic disorder affecting several organs including airways. Bacterial infection, inflammation and iron dysbalance play a major role in the chronicity and severity of the lung pathology. The aim of this study was to investigate the effect of lactoferrin (Lf), a multifunctional iron-chelating glycoprotein of innate immunity, in a CF murine model of Pseudomonas aeruginosa chronic lung infection. To induce chronic lung infection, C57BL/6 mice, either cystic fibrosis transmembrane conductance regulator (CFTR)-deficient (Cftr(tm1UNC)TgN(FABPCFTR)#Jaw) or wild-type (WT), were intra-tracheally inoculated with multidrug-resistant MDR-RP73 P. aeruginosa embedded in agar beads. Treatments with aerosolized bovine Lf (bLf) or saline were started five minutes after infection and repeated daily for six days. Our results demonstrated that aerosolized bLf was effective in significantly reducing both pulmonary bacterial load and infiltrated leukocytes in infected CF mice. Furthermore, for the first time, we showed that bLf reduced pulmonary iron overload, in both WT and CF mice. In particular, at molecular level, a significant decrease of both the iron exporter ferroportin and iron storage ferritin, as well as luminal iron content was observed. Overall, bLf acts as a potent multi-targeting agent able to break the vicious cycle induced by P. aeruginosa, inflammation and iron dysbalance, thus mitigating the severity of CF-related pathology and sequelae.